Updated inventory and ecological impacts of non-native fish in the Caspian Sea Basin: a systematic review of historical invasion pathways - Azad Teimori; Hamid Reza Esmaeili; Boris Levin; Keyvan Abbasi; Ekaterina D. Vasil’eva (Hydrobiologia, 2026)

Morphology and geographic distribution of poorly studied lampreys (Eudontomyzon) from the Western Dvina basin - Anzhelika V. Kolotei; Boris A. Levin; Aleksandr O. Zvezdin (Environmental Biology of Fishes, 2026)

DNA barcoding resolves the identity and invasion pathway of the non-indigenous goby genus Rhinogobius (Gobiiformes: Oxudercidae) in the Caspian Sea basin, and reveals cryptic diversity within the native range - Azad Teimori; Hamid Reza Esmaeili; Keyvan Abbasi; Fereshteh Pourhosseini; Mina Motamedi; Namiq Mustafayev; Boris A. Levin (Regional Studies in Marine Science, 2026)

Correction: Liem’s paradox in parallel trophic diversifications of polyploid fish: from preadaptive polymorphism to trophic specialization - Boris A. Levin; Aleksandra S. Komarova; Alexei V. Tiunov; Alexander S. Golubtsov (Hydrobiologia, 2024)

Liem’s paradox in parallel trophic diversifications of polyploid fish: from preadaptive polymorphism to trophic specialization - Boris A. Levin; Aleksandra S. Komarova; Alexei V. Tiunov; Alexander S. Golubtsov (Hydrobiologia, 2024)

Scale morphology is a promising, additional tool for exploring the taxonomy and ecology of freshwater fishes - Bálint Bánó; Aleksey Bolotovskiy; Boris Levin; George M. T. Mattox; Mauricio Cetra; István Czeglédi; Péter Takács (Fish and Fisheries, 2024)
It has long been recognized that presence–absence, localisation, size, number and shape of fish scales can be important taxonomic features. Although there are some notes on the relationship between scale morphology and ecological needs, in the absence of a sufficiently large and detailed database, the morphological variability of fish scales and the factors responsible for this variability have not yet been explored in detail. For this reason, a database—which contains the shape and relative size data of 193 freshwater fish taxa of 14 orders, originated from five biogeographic realms—has been built. Database analyses showed that both the scale shape and relative size are proper taxonomic indicators. They can be used to separate higher taxonomic categories (e.g., orders), and by the simultaneous analysis of shape and size scale morphology, we showed increased sensitivity for species‐level detachments. Our results suggest that while both the shape and the size of the fish scales are genetically determined, they are also useful descriptors of the niche segregation (habitat use, flow preference) of close relative species. Scale morphology is a promising additional tool to specify the environmental preferences of lesser known or close relative recent and extinct fish species. And also can be of great help in such cases when only the scales are available for taxonomic identification, for example, in the research field of archaeology and palaeontology.

Resource-Efficient Gigawatt Water Electrolysis in Germany—A Circular Economy Potential Analysis - Levin Matz; Boris Bensmann; Richard Hanke-Rauschenbach; Christine Minke (Circular Economy and Sustainability, 2024)
Green hydrogen will play a key role in the future energy system. For the production of green hydrogen, an installation of alkaline (AWE) and proton exchange membrane water electrolysis (PEMWE) of several gigawatts per year is projected in the upcoming decades. The development of the hydrogen economy is associated with a great demand for scarce and expensive resources. To reduce resource demand and avoid supply bottlenecks, actions toward a circular economy are required. In the present study, three circular economy actions (repair, reuse, and recycling) are analyzed with regard to AWE and PEMWE installation taking Germany as an example. It is found that, so far, only recycling is a viable strategy for a circular economy. For further analysis, a model is developed to assess the impact of recycling on resource demand for AWE and PEMWE scale-up. Mass flows from end-of-life recycling are intergrated into the model, and their economic value is estimated. The results imply that closed-loop recycling can reduce the cumulated primary resource demand by up to 50% in the long run. However, recycling will first be relevant after 2040, while water electrolysis capacities installed before still depend on primary materials. The outlook on the economic value of the recycling materials indicates a volume of up to 2.15 B € per decade for PEMWE and 0.98 B € per decade for AWE recycling. To realize the potential, a recycling industry specialized for those technolgies considering the whole value chain covering dismantling, collection, and recycling must be introduced.

Biogeographic insights from a genomic survey of Salmo trouts from the Aralo-Caspian regions - Iraj Hashemzadeh Segherloo; Seyedeh Narjes Tabatabaei; Asghar Abdoli; Jörg Freyhof; Eric Normandeau; Boris Levin; Matthias F. Geiger; Martin Laporte; Eric Hallerman; Louis Bernatchez (Hydrobiologia, 2022)

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

Rapid adaptive radiation in a hillstream cyprinid fish in the East African White Nile River basin - Boris Levin; Evgeniy Simonov; Paolo Franchini; Nikolai Mugue; Alexander Golubtsov; Axel Meyer (Molecular Ecology, 2021)
Adaptive radiation of freshwater fishes was long thought to be possible only in lacustrine environments. Recently, several studies have shown that riverine and stream environments also provide the ecological opportunity for adaptive radiation. In this study, we report on a riverine adaptive radiation of six ecomorphs of cyprinid hillstream fishes of the genus Garra in a river located in the Ethiopian Highlands in East Africa. Garra are predominantly highly specialized algae‐scrapers with a wide distribution ranging from Southeast Asia to West Africa. However, adaptive phenotypic diversification in mouth type, sucking disc morphology, gut length and body shape have probably been found among these ecomorphs in a single Ethiopian river. Moreover, we found two novel phenotypes of Garra (“thick‐lipped” and “predatory”) that had not been discovered before in this species‐rich genus (>160 species). Mitochondrial and genome‐wide data suggest monophyletic, intrabasin evolution of Garra phenotypic diversity with signatures of gene flow from other local populations. Although sympatric ecomorphs are genetically distinct and can be considered to being young species as suggested by genome‐wide single nucleotide polymorphism data, mitochondrial DNA was unable to identify any genetic structure suggesting recent and rapid speciation events. Some data suggest a hybrid origin of the novel “thick‐lipped” ecomorph. Here we highlight how, driven by ecological opportunity, an ancestral trophically highly specialized lineage is likely to have rapidly radiated in a riverine environment promoted by the evolution of novel feeding strategies.

Trophic resource partitioning by sympatric ecomorphs of Schizopygopsis (Cyprinidae) in a young Pamir Mountain lake: preliminary results - Aleksandra S. Komarova; Oksana L. Rozanova; Boris A. Levin (Ichthyological Research, 2021)

Characterization of Localities with a High Likelihood of Illicit Connections between Runoff and Sewage Systems - Rivka Levin; Mashor Housh; Boris A. Portnov (Environmental Management, 2020)

Taxonomic diversity of spined loaches (Cobitidae: Cobitis) in the Caucasus - Ekaterina Vasilyeva; Evgeniya Solovyeva; Boris Levin; Victor Vasil’ev (Frontiers in Marine Science, 2019)

Hybridization of Caucasian barbels of the genus Barbus s. str. - Boris Levin; Gandlin Alexander (Frontiers in Marine Science, 2019)

Sympatric assemblage of cyprinid fishes of the genus Garra (Cyprinidae) from the Sore River, White Nile basin, East Africa: is it a species flock? - Boris Levin; Evgeniy Simonov; Paolo Franchini; Axel Meyer; Alexander Golubtsov (Frontiers in Marine Science, 2019)

Adaptive radiation of labeobarbs (Labeobarbus; Cyprinidae) in the Genale River, East Africa: is this pure sympatric speciation? - Boris Levin; Miriam Casal-López; Evgeniy Simonov; Yury Dgebuadze; Nikolai Mugue; Alexei Tiunov; Ignacio Doadrio; Alexander Golubtsov (Frontiers in Marine Science, 2019)

High-throughput sequencing of the mitochondrial genomes from archived fish scales: an example of the endangered putative species flock of Sevan trout Salmo ischchan - Boris Levin; Evgeniy Simonov; Sergey Rastorguev; Eugenia Boulygina; Fedor Sharko; Svetlana Tsygankova; Bardukh Gabrielyan; Haikaz Roubenyan; Richard Mayden; Artem Nedoluzhko (Hydrobiologia, 2018)

Erratum to: A novel bedside test for ACPA: the CCPoint test is moving the laboratory to the rheumatologist’s office - Gisele Zandman-Goddard; Alessandra Soriano; Boris Gilburd; Merav Lidar; Shaye Kivity; Ron Kopilov; Pnina Langevitz; Yehuda Shoenfeld; Nancy Agmon-Levin (Immunologic Research, 2017)

A novel bedside test for ACPA: the CCPoint test is moving the laboratory to the rheumatologist’s office - Gisele Zandman Goddard; Alessandra Soriano; Boris Gilburd; Merav Lidar; Shaye Kivity; Ron Kopilov; Pnina Langevitz; Yehuda Shoenfeld; Nancy Agmon-Levin (Immunologic Research, 2017)

Genetic revision of Caucasian barbels, the genus Barbus: one species plus, one species minus - Levin Boris; Gandlin Alexander; Barmintseva Anna (Frontiers in Marine Science, 2015)

Thyroid hormone divergence as primary factor of speciation: evidences from phenotype and RNA-seq - Levin Boris; Bolotovskiy Aleksei; Levina Marina; Nedoluzhko Artem; Rastorguev Sergey (Frontiers in Marine Science, 2015)

Predictive value of anti-citrullinated peptide antibodies: a real life experience - Abdulla Watad; Nancy Agmon-Levin; Boris Gilburd; Merav Lidar; Howard Amital; Yehuda Shoenfeld (Immunologic Research, 2014)

Evaluation of an automated chemiluminescent immunoassay kit for antinuclear antibodies in autoimmune diseases - Yaron Zafrir; Boris Gilburd; Marina Garcia Carrasco; Shaye Kivity; María Sánchez-Castañón; Marcos López-Hoyos; Mathilda Mandel; Magdalena Szmyrka; Yehuda Shoenfeld; Nancy Agmon-Levin (Immunologic Research, 2013)

Threatened Fishes of the World: Barbus goktschaicus Kessler, 1877 (Cyprinidae) - Boris A. Levin; Haikaz R. Rubenyan (Environmental Biology of Fishes, 2006)